Treatment of Female Sexual Dysfunction Due to Dyspareunia with Solid-State Vaginal Laser and Recombinant Platelet-Derived Epidermal Growth Factors: A Viable Possibility? - Nicolas Mendoza; Francisco Quereda (Clinical and Experimental Obstetrics & Gynecology)
Objective: To examine the efficacy and safety of non-pharmacological and non-ablative options (or a combination of these) for postmenopausal dyspareunia. Mechanism: Narrative review on non-pharmacological and non-ablative options (or a combination of these) for postmenopausal dyspareunia. Findings in Brief: Dyspareunia is the most bothersome symptom of the genitourinary syndrome of menopause, often complicated by decreased sexual interest and arousal. Solid-state vaginal laser (SSVL) and recombinant platelet-derived epidermal growth factors (RGFs) are new alternatives are new alternatives that improve female sexual dysfunction resulting from dyspareunia. Conclusions: SSVL is a new alternative the treatment of postmenopausal dyspareunia either alone or in combination with other alternatives with efficacy and safety similar to the classical options.